Living without my foods: African Students Eating Habits Compared to All in the United States of America (Higher Education Politics and Economics, 2023)
The current project measures international students’ dietary acculturation challenges focusing on sub-Saharan Africans in the U.S.A. The analysis of 142 self-administered survey from participants between 18 and 48 are examined. Findings propose that students chose their foods when available. Newly arrived participants searched for known produce. Adaptation process starts after living for more than twenty-five months in the U.S. Sub-Saharan students increased their intake of standard American diet such as pre-made meals but reduced what they grew up eating. The surprise is that they shifted habits even when foods from their home countries are in groceries near them. Considering all, findings demonstrate that eating adjustment are related to length of stay, relationships, and food from their country of origin.